Pengaruh Terapi Musik Terhadap Perubahan Tanda-Tanda Vital Pada Pasien Post Operasi Fraktur Yang Mengalami Nyeri - Maksimilianus Lopes; Moh Alimansur; Edi Santoso (coba, 2014)
One of the factors that affect the frequency of the pulse is the emotion caused by acute pain and anxiety to increase sympathetic stimulation, it is can increase the frequency of the pulse, respiration rate, tension of blood. The purpose of this study was to determine the effect of music therapy on changes vital signs in patients postoperative fracture who experienced of pain in RSUD dr. Harjono Ponorogo. Design research is a one group pre - post test with Pre Experimental approach. The population studied were all patients postoperative fracture in dr. Harjono Ponorogo, by using a sampling technique accidental obtained sample was 26 respondents. The instrument used was observation. The results were analyzed using the Wilcoxon test (α = 0.05). The results showed Effects of music therapy on blood pressure with a significan p-value (0.002), pulse rate with p-Value (0.025), Respiratory with p-value (0.014), and that no significant is the body temperature p-value (0.180). This is because the music therapy can stimulate the production of serotonin that can stabilize vital signs. The conclusion of this study is blood pressure, pulse and respiration can be affected by music therapy..Advice for nurses is expected to provide music therapy to patients by giving the impression that the music is relaxing and beautiful so as to bring the patient to a state of relaxation. Keyword : Music Therapy, Vital Signs